STRATEGI SEKOLAH DALAM MEMBANGUN JIWA ENTERPRENEUR MELALUI P5 TEMA KEWIRAUSAHAAN KURIKULUM MERDEKA - Putri, Suriani Nanda; Riyanto, Yatim; Karoso, Subianto (Nindikayla Institute, 2023)
Education in Indonesia has undergone several curriculum changes, the latest of which is the Merdeka Curriculum. Apart from the teaching modules, one of the differences between the independent curriculum and other curricula is the existence of the Pancasila Student Profile Strengthening Project or often referred to as P5. One of the P5 themes is entrepreneurship. The method used is a qualitative method with the aim of describing descriptive data related to the strategies used by school principals in building an entrepreneurial spirit through the Independent Curriculum Strengthening the Pancasila Student Profile (P5) Project. In implementing the P5 project, 3 stages are used, including: inspiration, creation and dedication. All stages ran smoothly and the P5 project activities with the entrepreneurship theme were also successfully held.